Exchange Rates, Stock Prices, and Commodity Prices: Are There Any Relationships? - Kurihara, Yutaka; Fukushima, Akio (Advances in Social Sciences Research Journal, 2014)
<span style="font-family: 'Calibri','sans-serif'; font-size: 12pt; mso-fareast-font-family: 'ＭＳ 明朝'; mso-fareast-theme-font: minor-fareast; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: JA; mso-bidi-language: AR-SA;" lang="EN-US">After the financial crisis of 2008, commodity (e.g. gold) transactions have received much attention along with the rising prices instead of currencies such as the US dollar. On the other hand, the relationship between stock prices and exchange rates has been analyzed in the past; however, the findings seem ambiguous and no consensus about the relationship has been obtained yet. The relationship varies depending on the time, currency, kinds of stocks, and so on. One reason is the omission of commodity prices. The relationship between exchange rate and commodity prices and also the relationship between commodity prices and stock prices should be taken into account when analyzing the relationship between exchange rate and stock price.